Leveraging Digital Technologies in Logistics 4.0: Insights on Affordances from Intralogistics Processes - Tobias Albrecht; Marie-Sophie Baier; Henner Gimpel; Simon Meierhöfer; Maximilian Röglinger; Jörg Schlüchtermann; Lisanne Will (Information Systems Frontiers, 2023)
Emerging digital technologies are transforming logistics processes on a large scale. Despite a growing body of knowledge on individual use cases ranging from collaborative robots to platform-based planning systems in the frontline industrial development of Logistics~4.0, organizations lack a systematic understanding of the opportunities digital technologies afford for logistics processes. To foster such understanding, this study takes an intra-organizational perspective as a central starting point for digitalization initiatives toward Logistics~4.0. It synthesizes current academic research and industrial insights from a systematic literature review and an expert interview study through an affordance lens. The result is a catalog and conceptual framework of ten digital technology affordances in intralogistics (DTAILs) and 46 practical manifestations. Thereby, this study contributes to understanding and leveraging the opportunities digital technologies afford in a leading-edge information systems application domain. It serves as a foundation for further theorizing on Logistics 4.0 and for structuring strategic discussions among organizational stakeholders.
Keywords: 000; Affordance theory; Digital technology; Industry 4.0; Logistics 4.0; Logistics process; Supply chain management